The obsession - Roberts, Nora, frey50 (New York Berkley Books, 2016)
Years after discovering her father's predatory double life, successful photographer Naomi Bowes struggles to hide her painful past from her fellow residents in a community thousands of miles away, a situation that introduces her to a new relationship and forces her to confront her demons.
In freeing the woman trapped in the root cellar, Naomi Bowes revealed the horrible extent of her father's crimes, made him infamous... and discovered she can't outrun his sins. Now a successful photographer under the name Naomi Carson she has found a place that calls to her: a rambling old house in need of repair offers the solitude she seeks. But the kindly residents of Sunrise Cove keep forcing her to open up-- especially the determined Xander Keaton. Her new life offers something she's always secretly craved... but her past is never more than a nightmare away....
Keywords: Man-woman relationships; Fathers and daughters; Man-woman relationships; Fiction; Love stories; Romance fiction